Avaliando o sentido de vida e a resiliência no enfrentamento da pandemia da covid-19 - Monteiro, Tatiana Medeiros Costa (2023)
The Covid-19 pandemic was caused by a virus found in China in the second half of 2019 and, was characterized by individuals experiencing symptoms such as fever, dry cough, and difficulty breathing. However, some infected individuals exhibited mild symptoms or remained asymptomatic. Covid-19 led to a collapse of the healthcare systems in several nations, including Brazil, and to address this issue, the country implemented measures such as social distancing and established regulations on people's movement. These measures, combined with the uncertainties surrounding the pandemic and the severity of the symptoms, impacted people's mental health. The process of immunization brought a sense of hope and a fresh start; however, many people lost family members and/or friends, contracted the Covid-19 virus, were hospitalized, faced social distancing, and experienced economic crises due to business closures, among other challenges. For these reasons, it is crucial to evaluate the consequences left by this pandemic. Within this context, it appears crucial to assess post-traumatic stress and post traumatic growth. Furthermore, in this scenario, the sense of life and resilience may play an important role in understanding people's reactions after experiencing a potentially traumatic event. A study was conducted with the participation of 300 individuals ranging in age from 18 to 72 years (M = 37.8; SD = 11.94). The majority were females (77.3%), married or in a stable relationship (51.3%), and had completed postgraduate education (39.3%), with 60.3% indicating they had contracted Covid-19. Participants responded to scales assessing depression, anxiety, stress, post-traumatic stress, post-traumatic growth, meaning in life, and resilience, as well as sociodemographic characterization questions. Among the main findings, it was observed that meaning in life and resilience explained post-traumatic growth and post-traumatic stress, respectively. Resilience and meaning in life also explained other mental health outcomes (e.g., depression, anxiety, and stress). The importance of demographic variables in explaining mental health, as well as Covid-19-related variables that affected individuals, such as symptom severity, which directly impacted growth and post-traumatic stress and indirectly influenced negative affectivity, was also observed. In conclusion, the results obtained will enable interventions considering resilience as a predictor of post-traumatic stress and meaning in life as predictors of growth. Such variables can be explored in interventions with patients who had Covid-19 and are still suffering from the psychological consequences of the pandemic, aiming to alleviate suffering and maximize well-being.